IR-61 Improves Voiding Function via Mitochondrial Protection in Diabetic Rats - Wang, Jianwu; Dai, Linyong; Yue, Xiaofeng; Shen, Chongxing; Li, Tong; Long, Lei; Zhi, Yi; Wang, Yawei; Shen, Gufang; Shi, Chunmeng; Liu, Yunsheng; Fang, Qiang; et al. (Frontiers in Pharmacology, 2021)
Diabetic bladder dysfunction (DBD) afflicts nearly half of diabetic patients, but effective treatment is lacking. In this study, IR-61, a novel heptamethine cyanine dye with potential antioxidant effects, was investigated to determine whether it can alleviate DBD. Rats were intraperitoneally injected with IR-61 or vehicle after diabetes was induced with streptozotocin. Before evaluating the effects of IR-61 in improving DBD by filling cystometry, its distribution in tissues and subcellular organelles was detected by confocal fluorescence imaging. Near infrared (NIR) imaging showed that IR-61 could accumulate at high levels in the bladders of diabetic rats, and confocal images demonstrated that it was mainly taken up by bladder smooth muscle cells (BSMCs) and localized in mitochondria. Then, filling cystometry illustrated that IR-61 significantly improved the bladder function of diabetic rats. The histomorphometry results showed that IR-61 effectively mitigated the pathological changes in bladder smooth muscle (BSM) in diabetic rats. Furthermore, IR-61 remarkably reduced the number of apoptotic BSMCs and reversed the unfavorable expression of proteins related to the mitochondrial apoptotic pathway (Bcl-2, BAX, Cytochrome C and cleaved Caspase-9) in diabetic rats. Moreover, the frozen section staining and transmission electron microscopy results proved that IR-61 significantly reduced the reactive oxygen species (ROS) levels and reversed the mitochondrial mass and morphology damage in the BSM of diabetic rats. In addition, IR-61 upregulated the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and its associated antioxidant proteins in the BSM of diabetic rats. Together, these results indicate that IR-61 can improve the voiding function of rats with DBD by protecting the mitochondria of BSMCs from oxidative stress, which is possibly mediated through the activation of the Nrf2 pathway.